Taxes and Turnout: When the Decisive Voter Stays at Home - Bierbrauer, Felix; Tsyvinski, Aleh; Werquin, Nicolas (American Economic Review, 2022)
We develop a model of political competition with endogenous turnout and endogenous platforms. Parties trade off incentivizing their supporters to vote and discouraging the supporters of the competing party from voting. We show that the latter objective is particularly pronounced for a party with an edge in the political race. Thus, an increase in political support for a party may lead to the adoption of policies favoring its opponents so as to asymmetrically demobilize them. We study the implications for the political economy of redistributive taxation. Equilibrium tax policy is typically aligned with the interest of voters who are demobilized. (JEL D63, D72, H23, H24)